Prospective multicentre cross-sectional audit among older Australians accessing health and residential aged care services: protocol for a national advance care directive prevalence study. Issue 10 (28th October 2019) - Detering, Karen M; Buck, Kimberly; Sellars, Marcus; Kelly, Helana; Sinclair, Craig; White, Ben; Nolte, Linda
Abstract : Introduction: Advance care planning (ACP), an ongoing communication and planning process, aims to clarify a person's values and preferences, so these guide decision-making if the person becomes unable to make his or her own decisions. Ideally, ACP results in completion of advance care directives (ACD), documents completed by competent people outlining their values, treatment preferences and/or appointment of a substitute decision-maker (SDM). ACDs are most effective at the point of care, where they can be used to inform treatment decisions. Australian governments fund initiatives and have developed policy to increase ACD completion rates. However, little is known about the prevalence of ACDs at the point of care in Australian health services, making ACP evaluation efforts difficult. This study aims to determine the prevalence of ACDs in records of older people in Australian hospitals, aged care facilities and general practices. Methods and analysis: This is a national multicentre cross-sectional prevalence study in selected aged care facilities, hospitals and general practices. Following a 2017 feasibility study, a new protocol incorporating key learnings was developed. Sites will be recruited via expression of interest process. Health records of people aged ≥65 years, admitted to or attending services on study day(s) will be audited by trained staff from sites. Site-level data will be collected during the expression of interest. The primary outcome is the presence of at least one ACD in the health record. Secondary outcomes include prevalence of other documented outcomes of ACP (by health practitioner(s)/family/SDM), assessment of ACD quality and content and concordance between the person's documented preferences and any medical treatment orders. Individuals and sites characteristics where ACDs are present will be explored. Ethics and dissemination: Protocol approval by Austin Health Human Research Ethics Committee, Melbourne, Australia (reference: HREC/18/Austin/109). Results will be disseminated via peer-reviewed journals and conferences. Participating sites and jurisdictions will receive individualised reports of findings.